Human Wharton’s jelly mesenchymal stem cells-derived secretome could inhibit breast cancer growth in vitro and in vivo - Mansoureh Mirabdollahi; Hojjat Sadeghi-aliabadi; Shaghayegh Haghjooy Javanmard (Iranian Journal of Basic Medical Sciences, 2020)
Objective(s): Controversial results have been reported regarding the anti-tumor properties of extracellular vesicles derived from mesenchymal stem cells (MSCs). The present study was conducted to evaluate whether secretome derived from Human Wharton’s jelly mesenchymal stem cells (hWJMSCs) may stimulate or inhibit breast cancer growth in vitro and in vivo. Materials and Methods: MTT assays was performed to determine anti-tumor effects of hWJMSCs-secretome on both MCF-7 and 4T1 tumor cells in vitro. Afterward, 4T1 breast tumors were established in different groups of Balb/C mice (12 mice/group). The tumor sizes were monitored in different treatment groups and at day 30 post-tumor inoculation (PTI), blood samples were obtained and 6 mice of each group were sacrificed for hematological and histopathological assays. The rest of the mice in each group (n=6) were left alive up to day 120 PTI to determine survival rate. Results: We found that hWJMSCs-secretome can inhibit growth of MCF-7 and 4T1 tumor cell lines in vitro. Moreover, intratumoral administration of hWJMSCs-secretome resulted in signiﬁcant tumor growth inhibition and improvement of hematological indices in vivo and prolonged survival rate of tumor bearing mice. Conclusion: According to our findings, hWJMSCs-secretome could be considered a potent anti-tumor agent, however, further investigation should be done on other cancer models.